Volkameria inermis, a New Larval Host Plant of Common Shot Silverline Spindasis ictis (Lepidoptera: Lycaenidae) in India - Chaudhary, Rajesh; Dey, Shantanu (Journal of the Bombay Natural History Society (JBNHS), 2023)
No abstract